A Robust Control Scheme for a PVTOL System Subject to Wind Disturbances. (1st September 2020) - Merlo-Zapata, Carlos Alejandro; Aguilar-Ibanez, Carlos; Gutiérrez-Frías, Octavio; Antonio-Cruz, Mayra; Márquez-Sánchez, Celso; Suarez-Castanon, Miguel S.
Abstract : In this study, a control scheme that allows performing height position regulation and stabilization for an unmanned planar vertical take-off and landing aerial vehicle, in the presence of disturbance due to wind, is presented. To this end, the backstepping procedure together with nested saturation function method is used. Firstly, a convenient change of coordinates in the aerial vehicle model is carried out to dissociate the rotational dynamics from the translational one. Secondly, the backstepping procedure is applied to obtain the height position controller, allowing the reduction of the system and expressing it as an integrator chain with nonlinear disturbance. Therefore, the nested saturation function method is used to obtain a stabilizing controller for the horizontal position and roll angle. The corresponding stability analysis is conducted via the Lyapunov second method. In addition, to estimate the disturbance due to wind, an extended state observer is used. The effectiveness of the proposed control scheme is assessed through numerical simulations, from which convincing results have been obtained.